The Coptic divorce struggle in contemporary Egypt. (September 2019) - Elsässer, Sebastian
Since his accession in 2012, Coptic Orthodox Pope Tawadros II has initiated a number of reforms within the church, including a major overhaul of the church court system and the introduction of more liberal provisions concerning divorces. This article explores the historical development and current state of divorce and divorce law within the Coptic Orthodox Community in Egypt and the complex interactions between Coptic citizens, their church, and state courts. Scrutinising interviews and press statements by the new pope and senior clerics, it investigates their ideas of Coptic family law and their justification for changing the Church's approach to the divorce issue. It also takes the perspective of divorced Copts and looks at the myriad paths people have been following in search of legal and administrative loopholes, and assesses the impact that the new regulations will have on their lives.